Postpyloric Feeding Access in Infants and Children: A State of the Art Review. Issue 3 (9th August 2022) - Jazayeri, Amir; McConnie, Randolph M; Ross, Albert M; Montijo-Barrios, Ericka; Ballengee Menchini, Cortney; Tulin-Silver, Sheryl; Duron, Vincent; Walsh, Catharine M.; Lerner, Diana G.; Mencin, Ali
Abstract : Achieving postpyloric feeding access is a clinical challenge faced by the pediatric gastroenterologist in everyday practice. Currently, there is limited literature published on the topic. This article provides a practical summary of the literature on the different methods utilized to achieve postpyloric feeding access including bedside, fluoroscopic, endoscopic and surgical options. Indications and complications of these methods are discussed as well as a general approach to infants and children that require intestinal feeding.